Sixth Review of the Fund's Data Standards Initiatives : Metadata Standardization in the Data Quality Program. (Policy Papers; Policy Paper ;, 2005)
This Supplement describes how the staff proposes to achieve further synergies by mapping the DQAF into the metadata structure of the DQP's other key component: (3) the data transparency initiatives comprising the Special Data Dissemination Standard (SDDS) and General Data Dissemination System (GDDS).